Layanan Pendidikan Bagi Anak Tunagrahita Dengan Tipe Down Syndrome - Mayasari, Novi (Yinyang: Jurnal Studi Islam Gender dan Anak, 2019)
One of abnormalities in children in terms of mental retardation is down syndrome. Down syndrome is a mental retardation disorder in which the IQ is below normal average. Children with down syndrome have mental retardation function of intellectuals in the range of middle inability with the lateral range of IQ is 40-45. The cause of down syndrome is the abnormalities of chromosome number 21 which is not properly composed of two chromosomes. In fact, there are three chromosomes (trisomy 21) that cause the children to experience the physical and intellectual malformation. Mental retardation children with down syndrome experience some barriers to achieve the developmental tasks of cognitive, affective, and psychomotor aspects. However, they can still develop a non-academic potency such as taking care of themselves, making friends, and appreciating others’ property rights. Children who grow up with the abnormalities like as down syndrome have the same rights to obtain adequate educational services. Therefore, some educational services programs that can be arranged for the children with mental retardation of down syndrome are classroom-supports and guidance for them through visual and graphic approaches, cues-prompts and scaffolding, technology-based learning, and music-based learning.